2022
DOI: 10.3389/fmolb.2022.795212
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Expression to Probe Co-Translational Insertion of an Alpha Helical Membrane Protein

Abstract: The majority of alpha helical membrane proteins fold co-translationally during their synthesis on the ribosome. In contrast, most mechanistic folding studies address refolding of full-length proteins from artificially induced denatured states that are far removed from the natural co-translational process. Cell-free translation of membrane proteins is emerging as a useful tool to address folding during translation by a ribosome. We summarise the benefits of this approach and show how it can be successfully exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 133 publications
(182 reference statements)
0
5
0
Order By: Relevance
“…Synthetic membranes, in the form of liposomes and nanodiscs, have been used in CFE systems to improve expression of membrane proteins [17]- [20]. Experiments have established that membrane composition, available membrane area, and formation of co-translational membrane-bound ribosome complexes are crucial for successful CFE of membrane proteins [18], [21], [22]. However, each of the properties must be tuned to effectively produce properly folded, functional membrane proteins, limiting the ready adoption of membrane proteins into CFE systems [17], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic membranes, in the form of liposomes and nanodiscs, have been used in CFE systems to improve expression of membrane proteins [17]- [20]. Experiments have established that membrane composition, available membrane area, and formation of co-translational membrane-bound ribosome complexes are crucial for successful CFE of membrane proteins [18], [21], [22]. However, each of the properties must be tuned to effectively produce properly folded, functional membrane proteins, limiting the ready adoption of membrane proteins into CFE systems [17], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the E. coli SecYEG translocon has been shown to require cardiolipin (CL) to function optimally in vivo [ 119 ]. It has recently been demonstrated that the insertion yield of the bacterial leucine transporter (LeuT) expressed in vitro is significantly improved when both SecYEG and CL are present, but not when either CL or the translocon are included alone [ 120 ]. This study highlights that particularly when moving towards more ‘native-like’ IVTT systems, the effects of lipid composition on chaperone function, as well as on insertion and folding, must be considered.…”
Section: Methods To Investigate Co-translational Foldingmentioning
confidence: 99%
“…The PURE system has the advantage of being composed of well-defined components, and it has thus found wide application in bottom-up synthetic biology. ,, However, membrane proteins synthesized in vitro by transcription-translation with PURE tend to display low activities, partly due to limitations intrinsic to PURE (Box ) and partly due to the lack of control over protein insertion and folding. A number of studies have reported that polytopic membrane proteins self-insert into membrane bilayers when expressed cotranslationally, provided that specific phospholipid requirements are met. ,,, However, little or no quantitative information about the activity of the self-inserted membrane proteins is available (Box ). Thus, the synthesis of membrane proteins in vitro should be inspired by living cells, which couple the translation of membrane proteins to their insertion (i.e., transertion) into the lipid bilayer.…”
Section: Membrane Modules For a Bottom-up Minimal Metabolismmentioning
confidence: 99%
“…A number of studies have reported that polytopic membrane proteins self-insert into membrane bilayers when expressed cotranslationally, provided that specific phospholipid requirements are met. 68 , 69 , 220 , 221 However, little or no quantitative information about the activity of the self-inserted membrane proteins is available ( Box 3 ). Thus, the synthesis of membrane proteins in vitro should be inspired by living cells, which couple the translation of membrane proteins to their insertion (i.e., transertion) into the lipid bilayer.…”
Section: Membrane Modules For a Bottom-up Minimal Metabolismmentioning
confidence: 99%